Analysis of voltage stability problems in power system - Noor Ropidah, Bujal (2014)
Voltage stability analysis is important in power system in order to maintain the power system equilibrium. This research focuses on the voltage stability analysis of the power system feeders at distribution and transmission systems. The voltage stability analysis is carried out on the basis of single feeder comprising of two-bus system using ABCD line parameters. The feeder’s voltage in distribution and transmission system has been monitored at lagging and leading load conditions for various power factors. Hence, the active power-voltage (P-V) curve and reactive power-voltage (Q-V) are used as tools to monitor the voltage stability at feeders. The plotting methods for PV and QV curves have been improved by using MATLAB applications software. The voltage critical, voltage regulation, voltage gap and line current are monitored at each load power factor. The results of P-V and Q-V curves show very high accuracy for both lagging and leading load condition and these results agree with previous research outputs. The voltage stability analysis incorporates the Graphical User Interface (GUI) for user friendly suitable for teaching, learning and training application. The GUI is implemented using MATLAB GUI and this software package is targeted for engineering students and practicing engineers.